Evaluasi atas Penerapan Akuntansi Dana Pensiun dalam Kaitannya dengan Asersi Manajemen : Studi Kasus pada PT. Taspen (Persero) Cabang Bogor - Sutarti, Sutarti; Christin, Angki (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
The aim of this research is to evaluate an implementation of Accountancy Pension Fund in a company and it is linked to asersi management whether the company has implemented Accountancy Pension Fund based on SAK generally which covers itâs composition and report to those who competent especially the company management. The result shows that the company has implemented Accountancy Pension Fund well. Itâs shown by the policy of accounting based on SAK no. 18. Not only the implementation of Accountancy Pension Fund, the company has also managed itâs fund well and it can be trusted by the company management and it always gives the financial statements regulary. The implementation of Accountancy Pension Fund has been alocated clearly and completely and it is proven by the records of every transaction in a journal and it is confirmed by the company management, especially by department of finance and finance administration of the company and it is served and expressed naturally. Keywods : Accountancy Pension Fund, Asersi Management.